2015
DOI: 10.1177/1060028015594812
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal Reactions Associated With Serotonergic Antidepressants

Abstract: Case reports associating serotonergic antidepressants with EPRs continue to be published. Practitioners are advised that monitoring for such is important. Rigorous research efforts are needed to better understand the clinical risk factors for these adverse drug reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 99 publications
0
34
0
9
Order By: Relevance
“…Over the years many case reports have associated extrapyramidal symptoms (EPS) with the use of antidepressants. All kinds of EPS are seen in patients taking antidepressants, but akathisia appears to be the most common presentation followed by dystonic reactions, parkinsonian movements and tardive dyskinesia [135]. Akathisia appears to be more common in younger patients as compared with the other EPS symptoms [136].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Over the years many case reports have associated extrapyramidal symptoms (EPS) with the use of antidepressants. All kinds of EPS are seen in patients taking antidepressants, but akathisia appears to be the most common presentation followed by dystonic reactions, parkinsonian movements and tardive dyskinesia [135]. Akathisia appears to be more common in younger patients as compared with the other EPS symptoms [136].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In a study by Hawthorne et al on cases with EPS related side effects, 80.2% of them were found to have SSRI use. 9 In another study, SSRI, as independent from the use of additional medications, were found to cause 2.2 times as many EPS related side effects regarding the other antidepressants. Paroxetine was also found to be the most related medication to EPS in the category of SSRI (49%) and among all antidepressants (38%).…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7][8][9] Therefore, the purpose of this study is to contribute to the literature on dyskinesia cases by presenting an involuntary choreiform dyskinesia case appearing in the extremities related to the addition of paroxetine on chlorpromazine. To our knowledge, this report is the first case report on the observation of extremity dyskinesia related to paroxetine use.…”
Section: öLmez Et Al 517mentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic interaction at the level of CYP450 metabolism may contribute to raise plasma antipsychotic concentrations. 51 Interestingly, antidepressants have also caused or aggravated restless legs syndrome. Miscellaneous nonneuroleptic drugs have been associated with a low risk of DIP: antiarrhythmics (amiodarone, procaine), acetylcholinesterase inhibitors, antibacterial (rifampicin), antiviral (acyclovir, vidarabine, antiretrovirals), and antifungal (amphotericin B) antibiotics, and hormones (thyroxine).…”
mentioning
confidence: 99%